2011
DOI: 10.1037/a0022937
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nicotine dose and nicotine dose expectancy on the cognitive and subjective effects of cigarette smoking.

Abstract: This study investigated the independent and interactive effects of nicotine dose and nicotine dose expectancy on smoking outcomes using a 2 (given nicotine vs. placebo) × 2 (told nicotine vs. placebo) Balanced Placebo Design (BPD). Smokers (N = 148) completed the Rapid Visual Information Processing Task (RVIP) and measures of smoking urge, mood, and cigarette ratings (e.g., satisfying) after smoking a nicotine or placebo cigarette crossed with instructions that the cigarette contained either nicotine or no nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 36 publications
6
71
1
Order By: Relevance
“…Interestingly, one PET study found that negative drug prediction errors (i.e., alcohol expected but not delivered) decreased striatal DA concentrations while positive drug prediction errors (i.e., alcohol not expected but delivered) increased striatal DA levels in individuals with alcohol dependence (21), which is consistent with our finding of modifiable striatal responses by beliefs. Furthermore, our findings extend previous results showing the impact of beliefs on behavioral performances and subjective states related to nicotine intake (15)(16)(17)20) by detailing the specific neural and computational mechanisms underlying the impact of beliefs on drug effects. These selective effects demonstrate that belief can modulate model-based parameters important for learning and suggest that belief serves as an important cognitive mechanism in addiction.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, one PET study found that negative drug prediction errors (i.e., alcohol expected but not delivered) decreased striatal DA concentrations while positive drug prediction errors (i.e., alcohol not expected but delivered) increased striatal DA levels in individuals with alcohol dependence (21), which is consistent with our finding of modifiable striatal responses by beliefs. Furthermore, our findings extend previous results showing the impact of beliefs on behavioral performances and subjective states related to nicotine intake (15)(16)(17)20) by detailing the specific neural and computational mechanisms underlying the impact of beliefs on drug effects. These selective effects demonstrate that belief can modulate model-based parameters important for learning and suggest that belief serves as an important cognitive mechanism in addiction.…”
Section: Discussionsupporting
confidence: 87%
“…We calculated the weight of market return r t on next bet b t+1 , using a linear mixed-effects multiple-regression model (details in Materials and Methods). Compared with when told nicotine, the regression coefficient of r t on next bet b t+1 was significantly reduced when subjects were told no nicotine [t (16,885) = 5.07, P < 0.0001, Fig. 2C; Table S3 shows list of all regressors], even though they smoked nicotine in both conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six targets/min were presented for 10 min with a response window of 800 ms. The variable of interest was A′, a measure of discriminability between targets and nontargets, rather than the number of hits or reaction times, as the former is more sensitive to effects of nicotine (Foulds et al, 1996;Juliano et al, 2011;Leventhal et al, 2010).…”
Section: Rapid Visual Information Processing Taskmentioning
confidence: 99%
“…Prior work has indicated that in 18-60 year-olds, smoking a cigarette delivering o0.1 mg nicotine alleviates craving and withdrawal less (albeit non-significantly) than a conventional cigarette (Buchhalter et al, 2001;Rose et al, 2000), but that cigarettes delivering~0.05 mg nicotine provide relief as effectively as conventional cigarettes when smoked ad libitum for 90 min (Dallery et al, 2003;Tidey et al, 2013) or 4 h (Eid et al, 2005). Further, performance on the Rapid Visual Information Processing task (RVIP), a test of sustained attention, indicated greater discriminability between targets and non-targets (indicating increased sustained attention) after smoking a cigarette delivering 0.6 mg nicotine vs a cigarette delivering 0.05 mg nicotine (Juliano et al, 2011), but performance before and after smoking was not compared.…”
Section: Introductionmentioning
confidence: 99%